Microstructures of barbels and bony plates of Satyrichthys laticeps (Actinopterygii: Peristediidae) - Ngamniyom, Arin (Journal of Fisheries, 2020)
Barbels are sensory-appendage near the mouth of many fishes including Cyprinidae, Ictaluridae and Peristediidae and commonly used for identification of the species. Similarly scales and bony plates of fishes also being used in taxonomic studies. Satyrichthys laticeps commonly called armoured searobins, is a deep-sea peristediid that distributed in the Indo-West Pacific region of the world. However, surface structures of has been unknown. The aim of this study is to reveal the microstructures of barbels and bony plates of S. laticeps, occurring in the Andaman Sea of Thailand, for the first time by using a scanning electron microscopy method. The chin barbels were characterised by a pebble-like surface whereas lip barbels resemble wooden texture. Taste bud-like organs were only visible in chin barbels. Bony plates from heads contained small semispheres around spine. In dorsolateral of posterior body, pits appeared at the apices, and semispherical buds were present in the middle and basal parts of tubercles. The study results may be important in understanding the physiology in peristediid fish.